Legal Protection for Consumers Using Transportation Services on The River - Hardianto, Irwansyah Rizki; Nasution, Krisnadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses legal protection for consumers who use river transportation services, which aims to ensure the safety and comfort of users. With a normative juridical approach, this study uses the analysis of laws and regulations and a conceptual approach to evaluate the implementation of laws in the river transportation sector. The results show that despite regulations that protect consumer rights, implementation in the field still faces various challenges. Many business actors do not comply with the Standard Operating Procedures (SOPs) that regulate passenger safety, exacerbated by the weak supervision and socialization from the government. This research recommends increased supervision, more effective socialization, and strict law enforcement to ensure that consumer rights are optimally fulfilled.